The Effect of Protein High Diet Consumption on Wound Healing in Mother Post Sectio Caesarea in The Breath Space RSUD Kota Langsa Provinsi NAD in 2017 - Safitri, Mey Elisa (Sari Mutiara Indonesia University Press, 2018)
Childbirth at caesarean section is not an operation that is feared by many women today. Sectio caesarea is a way of giving birth to the fetus by making an incision in the uterine wall through the front wall of the abdomen. One of the factors of wound healing is the fulfillment of nutrients, especially protein. The purpose of this study was to determine the effect of consumption of high protein diet on wound healing in post sectio caesarea mothers in the postpartum room of Langsa City Hospital, NAD Province in 2017. This study uses a quasi-experimental study design, dividing respondents into 2, namely the intervention group and the control group. The population in this study were all patients post sectio caesarea in the postpartum room of Langsa City Hospital as many as 30 respondents. Samples were taken using consecutive sampling using checklists and questionnaires. The results of the study were analyzed using bivariate analysis with test normality and homogeneity and test nonparametric. From the results of the study it is known that from 30 respondents there were 15 respondents (30%) in the intervention group recovered, while there were 8 respondents (26.6%) recovered, while there were 7 respondents (23.3%) did not recover. The results of the t- Independent test analysis show p value = 0.004 < α. Based on the results of the study and discussion, it can be concluded that there is an effect of high protein diit on wound healing in mothers post sectio caesarea . It is recommended that patients pay more attention to the intake of nutritious foods for healing wounds, especially those with high protein content, so that they can improve body cells that are injured due to surgery more quickly by consuming cork fish.